CD73/adenosine dynamics in treatment-induced pneumonitis: balancing efficacy with risks of adverse events in combined radio-immunotherapies - Gockeln, Lena; Wirsdörfer, Florian; Jendrossek, Verena (Frontiers in Cell and Developmental Biology, 2025)
Consolidation with PD-1/PD-L1-based immune checkpoint blockade after concurrent platinum-based chemo-radiotherapy has become the new standard of care for advanced stage III unresectable non-small cell lung cancer (NSCLC) patients. In order to further improve therapy outcomes, innovative combinatorial treatment strategies aim to target additional immunosuppressive barriers in the tumor microenvironment such as the CD73/adenosine pathway. CD73 and adenosine are known as crucial endogenous regulators of lung homeostasis and inflammation, but also contribute to an immunosuppressive tumor microenvironment. Furthermore, the CD73/adenosine pathway can also limit the immune-activating effects of cytotoxic therapies by degrading the pro-inflammatory danger molecule ATP, which is released into the tumor microenvironment and normal lung tissue upon therapy-induced cell damage. Thus, while targeting CD73 may enhance the efficacy of radio-immunotherapies in cancer treatment by mitigating tumor immune escape and improving immune-mediated tumor killing, it also raises concerns about increased immune-related adverse events (irAEs) in the normal tissue. In fact, combined radio-immunotherapies bear an increased risk of irAEs in the lungs, and additional pharmacologic inhibition of CD73 may further enhance the risk of overwhelming or overlapping pulmonary toxicity and thereby limit therapy outcome. This review explores how therapeutic interventions targeting CD73/adenosine dynamics could enhance radiation-induced immune activation in combined radio-immunotherapies, whilst potentially driving irAEs in the lung. We specifically investigate the interactions between radiotherapy and the CD73/adenosine pathway in radiation pneumonitis. Additionally, we compare the incidence of (radiation) pneumonitis reported in relevant trials to determine if there is an increased risk of irAEs in the clinical setting. By understanding these dynamics, we aim to inform future strategies for optimizing radio-immunotherapy regimens, ensuring effective cancer control while preserving pulmonary integrity and patient quality of life.